Ali Salman, Mohammad Hashim Kamali and Mohamed Azam Mohamed Adil (Editors) - Democratic transitions in the Muslim world (2018) - Mohamad Shukri, Syaza Farhana (2020)
Among Muslim-majority countries in the world today, only a handful can be said to be democracies. This puzzling fact has been investigated and written about by countless scholars in the past decades such as Olivier Roy, John Esposito, Asef Bayat and Daniel Brumberg, just to name a few. Following the tragic end of the 2010 Arab Uprisings (tragic for the current state of civil unrest and war ongoing in the Middle East), scholars from the East are now trying to make sense of this enigma regarding the relationship between Islam and democracy. To the writers in this edited book, Islam and democracy are not intrinsically antagonistic. The world around these authors seems to have accepted democracy, if not substantially, at least instrumentally as a peaceful mechanism to choose persons into power.